A novel thin-film transistor with step gate-overlapped lightly doped drain and raised source/drain design. (November 2017) - Chien, Feng-Tso; Chen, Jian-Liang; Chen, Chien-Ming; Chen, Chii-Wen; Cheng, Ching-Hwa; Chiu, Hsien-Chin
Highlights: A SGORSD-TFT without additional ion implantations and masks is discussed. This device can reduce device electric field, and suppress the kink effect. The SGORSD design can improve device reliability. Abstract: In this paper, a novel step gate-overlapped lightly doped drain (GOLDD) with raised source/drain (RSD) structure (SGORSD) is proposed for TFT electronic device application. The new SGORSD structure could obtain a low electric field at channel near the drain side owing to a step GOLDD design. Compared to the conventional device, the SGORSD TFT exhibits a better kink effect and higher breakdown performance due to the reduced drain electric field (D-EF). In addition, the leakage current also can be suppressed. Moreover, the device stability, such as the threshold voltage shift and drain current degradation under a high gate bias, is improved by the design of SGORSD structure. Therefore, this novel step GOLDD structure can be a promising design to be used in active-matrix flat panel electronics.